Revitalization of Social Media Communication Ethics in Building a Sublime and Civilized Indonesian Culture - Hani Yuniani; Mike Indarsih; Fajar Diah Astuti; Horidatul Bakiyah (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2023)
Humans are essentially the most adaptive creatures to the changes and developments of the times, especially in using technology in communicating. This is because technological developments are felt to be able to meet the needs and quality of life. The development and acceleration of the current 4.0 ways of communicating, has a side effect, namely the wider freedom of humans to express thoughts and feelings expressively as communicators. So that the boundaries that have been consistently understood and practiced for decades as guidelines for etiquette are now increasingly blurred and replaced with new phrases, icons, and emoticons as symbols of facial expressions. The courage of the communicators is also since social media allows communication participants to exchange messages without knowing their real identities/using anonymous accounts. This study aims to see and observe what kinds of conversations invite comments and have the potential to violate ethics. The method used is participatory observation and uses primary data, namely trending topics on Twitter social media. The findings are that the content that often invites reactions is conversations about religion, political choices, and statements that are considered lies. It is necessary to apply communication ethics on social media to become guidelines for cyber casting.